2017
DOI: 10.1055/s-0043-122386
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive intravenous hydration with lactated Ringer’s solution for prevention of post-ERCP pancreatitis: a prospective randomized multicenter clinical trial

Abstract: Background and study aims The present study aimed to determine the type of intravenous hydration that is best suited to reducing the incidence of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis. Patients and methods In a prospective randomized multicenter trial, average-to-high risk patients who underwent first-time ERCP were randomly assigned to three groups (1:1:1) who received: aggressive intravenous hydration (3 mL/kg/h during ERCP, a 20-mL/kg bolus and 3 mL/kg/h for 8 hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(67 citation statements)
references
References 30 publications
3
59
0
4
Order By: Relevance
“…In 2014, two hypothesis-generating retrospective studies reported that greater peri-procedural intravenous fluid volume was an independent protective factor against moderate to severe PEP 95 and was associated with shorter hospital LOS 96 . Very recent meta-analyses and RCTs support using LR prior to ERCP to prevent PEP 97 100 and to reduce moderate to severe PEP 97 , 98 . Interestingly, a recent RCT shows that the combination of rectal indomethacin and LR compared with combination placebo and normal saline reduced the risk of PEP in high-risk patients 101 .…”
Section: Recent Advances In Early Treatment Of Acute Pancreatitismentioning
confidence: 99%
“…In 2014, two hypothesis-generating retrospective studies reported that greater peri-procedural intravenous fluid volume was an independent protective factor against moderate to severe PEP 95 and was associated with shorter hospital LOS 96 . Very recent meta-analyses and RCTs support using LR prior to ERCP to prevent PEP 97 100 and to reduce moderate to severe PEP 97 , 98 . Interestingly, a recent RCT shows that the combination of rectal indomethacin and LR compared with combination placebo and normal saline reduced the risk of PEP in high-risk patients 101 .…”
Section: Recent Advances In Early Treatment Of Acute Pancreatitismentioning
confidence: 99%
“…2). Other factors that impact risk of PEP, including intravenous hydration, procedural expertise, and procedural technique modification are not consistently reported in studies and might confound our study results [15,31].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, 100 mg of indomethacin was administered anally to all patients who did not have a history of allergy (17). Aggressive intravenous hydration (including 3 mL/kg/h during ERCP, a 20-mL/kg bolus, and 3 mL/kg/h for eight hours after ERCP) with lactated Ringer's solution was administered to all patients without contraindications (18). CBD stones were extracted using a balloon and/or basket catheter.…”
Section: Stages Of Acute Cholangitismentioning
confidence: 99%